The "Resource Curse" in MENA Political Transitions, Resource Wealth, Economic Shocks, and Conflict Risk - Ross, Michael (The World Bank, 2011)
The recent political upheavals in the Middle East and North Africa region have exposed growing concerns about conflict risk, political stability, and reform prospects across its societies. Given the prevalence of oil and gas resource endowments in the region, which a voluminous literature suggests can be associated with adverse development consequences, this paper examines the interplay between their associated rents and political economy trajectories. The contribution of the paper is threefold: first, to examine the quantitative evidence of violent conflict in the region since 1960; second, to provide a nuanced review of the regional case study literature on the relationship between resource endowments, political stability, and conflict risk; and third, to assess how prospective political transitions have implications for the World Bank Group's work in the region on public sector management and private sector development. The authors find that resources and regimes have intersected to provide stability and limited violent conflict in the region, but that these development patterns have yielded a set of policy choices and development patterns that are proving increasingly brittle and unsustainable. A major institutional challenge for reforms will be to consolidate a requisite degree of intertemporal credibility and stability in these regimes, while expanding inclusiveness in state-society relations